Preliminary results of corrosion monitoring studies of carbon steel overpack exposed to supercontainer concrete buffer. (September 2014) - Kursten, B.; Druyts, F.; Areias, L.; van Ingelgem, Y.; De Wilde, D.; Nieubourg, G.; Duffó, G. S.; Bataillon, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The supercontainer (SC) is the reference concept for the postconditioning of vitrified high level radioactive waste and spent fuel in Belgium. It is designed with a concrete buffer completely surrounding a carbon steel overpack. A half-scale (HST-2) experiment was set up to measure the instantaneous uniform corrosion rate, representative of the initial oxic phase, in situ. The test set-up has the same diameter as a full size SC, but it is limited in height to approximately half of a real SC. The corrosion rate of carbon steel is measured in four ways: weight loss measurements (carbon steel coupons), corrosion sensor based on linear polarisation resistance, corrosion sensor based on multisine electrochemical impedance spectroscopy and corrosion sensor based on single sine electrochemical impedance spectroscopy coupled to a unique analytical method. This paper presents the preliminary results of the corrosion rates measured with these independent methods.